Over a million students use our free study notes to help them with their homework
This can be rewritten as x1/2 + 4x-1/2+ 4, hence dy/dx = (1/2)x-1/2 - 2x-3/2
say (2x-π/6)=qtan2q = sec2q-1so sec2q-1= 11 - sec q sec2q + sec q -12 = 0(sec q -3) (sec q + 4) = 0sec q = 3 or -4because 0<=x<= πso -π/6 <= q <= 11...
eln(2x-3) = e12x-3 = ex = (e+3)/2
Assuming knowledge of solving regular quadratic equations.Treat this as a regular quadratic equation, except it is in terms of sin(x) instead of just x as you might be used to.So using the quadratic equat...
To answer this question you must use implicit differentiation due to there being both x and y terms. Consequently you must differentiate each term individually as you would usually (by multiplying by the ...
←
306
307
308
309
310
→
Internet Safety
Payment Security
Cyber
Essentials